Prospecção de transcritos codificadores de quitinases em dados de RNA-Seq da formiga cortadeira Atta sexdens - Flores, Lorrana Verdi (2023)
The leaf-cutting ant Atta sexdens is widely distributed in Brazil and is considered an important insect pest of several crops due to its intense foraging activity on fresh plant material. The intense defoliation performed by ants takes place to grow the symbiotic fungus (Leucoagaricus gongylophorus) on which ants feed. Although much is known about the ants bioecology, there are still few studies to validate the gene function of protein families that play important roles in the development of leaf-cutting ants, since little molecular data is currently available for these species. This work aimed to obtain the leaf-cutting ant A. sexdens transcriptome by RNA sequencing of five biological samples (whole larva, larval gut, whole foraging ant, head, and gut of foraging ant), aiming to identify sequences encoding chitinases – enzymes involved in the degradation route of chitin, a vital polysaccharide for building extracellular matrices and for accomplishing other functions in insects. After sequencing, de novo assembly of the transcripts was performed using the Trinity tool. The prediction of Open Reading Frames occurred from similarity data and identification of protein domains, with identification of 45,253 protein-coding sequences. Of this total, 36,639 sequences had at least one domain deposited in the Pfam database, and it was possible to annotate 24,392 sequences containing direct orthologs in databases available in eggNOG. In general, the transcripts present in larger quantities in A. sexdens transcriptome fell into the category signal transduction mechanisms. From the phylogenetic analysis, twenty-three sequences encoding chitinases were identified, divided into eleven groups of chitinases commonly found in insects, of which fifteen presented all the expected domains. Therefore, with the in silico identification of potencial candidates for chitinases in the A. sexdens transcriptome it will be possible to expand molecular and physiological knowledge about the species and contribute to further studies aimed at elucidating the role of these enzymes in the development of leaf-cutting ants.